HUBUNGAN LEMAK VISERAL TERHADAP TINGKAT RISIKO OBSTRUCTIVE SLEEP APNEA PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA TAHUN 2022 - Muhammad Ferrel Privansyah Cader (2023)
The COVID-19 pandemic caused changes in student lifestyles, triggering visceral fat accumulation. Deposits of visceral fat around the pharynx, trunk, and intra-abdominal can cause airway collapse and increase the risk of obstructive sleep apnea. The purpose of this study was to determine the relationship between visceral fat and the risk of obstructive sleep apnea among medical students. This study used a cross-sectional design on 55 Faculty of Medicine UPN "Veteran" Jakarta students who met the criteria and were selected using a simple random sampling technique. Tanita Body Composition Analyzer was used to measure visceral fat, while the risk of obstructive sleep apnea was measured using the STOP-BANG questionnaire. There were differences in BMI between the normal and high visceral fat groups (p = 0.000). There were no differences in age, sedentary behavior, and eating habits between the visceral fat groups (p > 0.05). Chi-Square exact test results showed a significant relationship between visceral fat and the risk of obstructive sleep apnea (p = 0.018). The conclusion of this study revealed a significant relationship between visceral fat and the risk of obstructive sleep apnea among medical students. Keyword: medical students, obstructive sleep apnea, visceral fat